Pain characteristics of temporomandibular disorder: a pilot study in patients with cervical spine dysfunction (Journal of Applied Oral Science, 2006)
OBJECTIVE: The purpose of the present pilot study was to describe pain complaints of TMD patients and cervical spine dysfunction. METHODS: Fourteen women with myogenous TMD, cervical motion limitation and rotation of at least one of the three first cervical vertebrae evidenced by radiographic examination participated in this study. The multidimensional pain evaluation was accomplished by a Brazilian version of the McGill Pain Questionnaire. RESULTS: The results showed that the most painful body site mentioned was cervical spine, followed by scapular region and temporomandibular joint. More than half of the volunteers reported temporal pain pattern as rhythmic, periodic and, or still, intermittent. The majority of the patients classified the pain intensity assessed at the moment of the evaluation as mild to discomforting. Absolute agreement was not observed among volunteers regarding word dimensions used to describe their pain, although a great number of patients chose the descriptor related to tension as the better expression to describe their painful complaint. CONCLUSION: Pain characteristics of TMD patients with cervical spine dysfunction showed cervical spine as a common painful region reported and words related to affective and emotional dimensions of pain perception can be used by these patients to qualify their pain complain.